Pancreatic insulinoma. Case report and review of the literature - NEGREAN, VASILE (Clujul Med, 2013)
Insulinoma is a rare pancreatic islet cell tumor, the most common cause of hypoglycemia related to endogenous hyperinsulinism. We present the case of an adult patient with pancreatic insulinoma. The patient presented to our clinic after prior hospitalizations in diabetes and psychiatry hospital units for repeated episodes of loss of consciousness, sweating and tonic-clonic seizures. Early detection of the cause is important for prompt initiation of therapy and to reduce symptoms. We describe our diagnostic and therapeutic strategies with references to previously published reports.